Comparison of vaginal self‐sampling and cervical sampling by medical professionals for the detection of HPV and CIN2+: A randomized study. Issue 12 (17th February 2021) - Aarnio, Riina; Isacson, Isabella; Sanner, Karin; Gustavsson, Inger; Gyllensten, Ulf; Olovsson, Matts
Abstract: Primary screening with human papillomavirus (HPV) test is more effective in reducing cervical cancer incidence than cytology and it also offers the opportunity to self‐sample. We conducted a randomized study to compare vaginal self‐sampling with cervical sampling by medical professionals for HPV testing concerning prevalence of HPV and detection of cervical intraepithelial neoplasia (CIN) of grade 2 or worse (CIN2+) or grade 3 or worse (CIN3+) in primary screening. In total, 11 951 women aged 30‐60 years were randomized into two groups, 5961 for self‐sampling (SS arm) and 5990 for sampling by medical professionals (SMP arm). Sampling was performed with a RoversViba‐brush in the SS arm and a cytobrush in the SMP arm. All samples were applied to an indicating FTA elute card and analyzed for HPV using a clinically validated real‐time PCR test (hpVIR). All HPV‐positive women performed repeated sampling about 6 months later using the same procedure as used initially. All HPV‐positive women in the second sampling were referred to colposcopy. The prevalence of HPV in the first test did not differ between the SS arm (6.8%, 167/2466) and the SMP arm (7.8%, 118/1519) ( P = .255). The prevalence of CIN2+ per 1000 screened women was 17 (43/2466 × 1000) (95%CI 13‐24) in the SS arm and 21 (32/1519 × 1000) (95%CI 15‐30) in the SMP arm. For CIN3+, the prevalence per 1000 screened women was 14 (35/2466 × 1000) (95%CI 10‐20) in the SS arm and 15 (23/1519 × 1000) (95%CI 10‐23) in the SMP arm. In conclusion, self‐sampling and sampling by medical professionals showed the same prevalence of HPV and detection rate of CIN2+ and CIN3+ in histology. Abstract : What's new? Primary screening with human papillomavirus (HPV) test is more effective in reducing cervical cancer incidence than cytology and offers the opportunity for self‐sampling. However, the feasibility and effectiveness of self‐sampling in primary screening should be further evaluated. Our study shows that, in women aged 30‐60 years, self‐sampling yields similar rates of HPV prevalence and CIN2+ and CIN3+ detection compared to sampling by medical professionals when using an FTA card as storage medium and PCR‐based HPV test. Considering health‐economics aspects, resources should be directed toward self‐sampling as a first choice for primary cervical screening, with careful follow‐up of this strategy.